Decisions, translation strategies and process in the translation of Molope's Dancing in the Dust : a critical analysis - Magwebu, Doris NomaXesibe (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2007.